2015
DOI: 10.1073/pnas.1504081112
|View full text |Cite
|
Sign up to set email alerts
|

Tau stabilizes microtubules by binding at the interface between tubulin heterodimers

Abstract: The structure, dynamic behavior, and spatial organization of microtubules are regulated by microtubule-associated proteins. An important microtubule-associated protein is the protein Tau, because its microtubule interaction is impaired in the course of Alzheimer's disease and several other neurodegenerative diseases. Here, we show that Tau binds to microtubules by using small groups of evolutionary conserved residues. The binding sites are formed by residues that are essential for the pathological aggregation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
375
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 441 publications
(393 citation statements)
references
References 56 publications
17
375
1
Order By: Relevance
“…S4). Our observation supports NMR studies, which suggest that the N terminus retains high flexibility in the taumicrotubule complex (33,35). We find key differences between the heparin-and tubulin-bound tau conformations as well, showing that, although the binding sites for heparin and tubulin or microtubules may be the same (40), the conformational changes on binding are not simply the result of tau binding to anionic molecules or surfaces but are distinct conformational differences between the aggregation-prone and functional forms of tau.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…S4). Our observation supports NMR studies, which suggest that the N terminus retains high flexibility in the taumicrotubule complex (33,35). We find key differences between the heparin-and tubulin-bound tau conformations as well, showing that, although the binding sites for heparin and tubulin or microtubules may be the same (40), the conformational changes on binding are not simply the result of tau binding to anionic molecules or surfaces but are distinct conformational differences between the aggregation-prone and functional forms of tau.…”
Section: Discussionsupporting
confidence: 89%
“…On the surface, this observation seems contradictory. However, it has been proposed that tau's interaction with microtubules is mediated by an array of short motifs within the MTBR, with flanking residues remaining flexible (33). If a similar model holds for tau bound to multiple tubulin dimers, then we can rationalize that binding to tubulin may cause local expansion in regions involved directly in binding, whereas the flexibility of the flanking regions allows the overall dimensions of the MTBR to be maintained.…”
Section: Discussionmentioning
confidence: 94%
“…This increase in the ensemble-averaged inner radius of MTs, <R in MT >, indicated that MT-associated protein Tau isoforms do not just bind and stabilize MTs, for example, by enhancing PF-PF interactions but also, change the shape of αβ-tubulin and thus, PFs, leading to a change in curvature of MTs. This conclusion is consistent with recent NMR work showing that Tau binds, at least in part, between tubulin heterodimers (31).…”
Section: Significancesupporting
confidence: 93%
“…1A, Left). Although Tau strongly binds to the MT surface (∼1-3 μM affinity) (10,26), recent work suggests that Tau-MT interactions are highly dynamic and that Tau can assume numerous structures (30,31).…”
Section: Significancementioning
confidence: 99%
“…With the ease of yeast genetics, both problems may be overcome. The failure of tau to bind to yeast tubulin is most likely due to sequence differences between yeast α-tubulin and its mammalian homolog, located at the proposed tau-binding site [102]. It may thus be possible to produce chimeric yeast/human microtubules in such a strain which can be employed for in vivo binding assays.…”
Section: Genetic Screens In Yeast -The Past the Present And The Futurementioning
confidence: 99%